KAJIAN KOMPOSISI LIGNIN DAN SELULOSA DARI LIMBAH KAYU SISA DEKORTIKASI RAMI DAN CANGKANG KULIT KOPI UNTUK PROSES GASIFIKASI DOWNDRAFT - Veni Aprilia Lestari; Trisaksono Bagus Priambodo (Badan Pengkajian dan Penerapan Teknologi, 2020)
Gasification of biomass can be used to produce fuel gas that could potentially be used as a powersource for the sustainable development. The main aim of this study is to determine the effect of lignin,cellulose, proximate and ultimate of ramie wood chip biomass and shell coffee to produce gas and thepotential for regional electricity generated. Research carried out by the analysis of lignin and cellulose,proximate and ultimate, calorific value, gasification, composition gases and energy potential. From theresearch results, the waste of coffee shells and ramie wood chips were used as a new energy source toproduce syngas by means of the gasification process. The highest lignin content was for 45.10% coffeeshell and the lowest for flax wood chips was 18.26. Meanwhile, the highest cellulose content was hempwood chips 44.82% and the lowest was coffee skin shell 17.93%. The potential energy produced fromgasified gas provides a correlation with levels of lignin and cellulose. The higher the lignin content andthe greater the cellulose content, the higher energy that occurs in the coffee shell shells of 5.78 kW, andvice versa what happens to hemp wood chips with low lignin levels and high cellulose content providesa potential energy of 4. 64 kW